Influence of dietary and physical activity restriction on pediatric adenotonsillectomy postoperative care in Brazil: a randomized clinical trial - Manica,Denise (2018)
Abstract Introduction Although culturally food and physical activity restriction are part of the routine postoperative care of many Brazilian surgeons, current evidences from other countries support no such recommendations. Objective To determine whether dietary and physical restriction effectively lead to a decrease on postoperative complications of adenotonsillectomy in children when compared to no restriction. Methods We have designed a randomized clinical trial comparing two intervention: no specific counseling on diet or activity (Group A), and restriction recommendations on diet and physical activities (Group B). Caregivers completed a questionnaire on observed pain, diet and activity patterns, and medications administered. Parameters were compared at the 3rd and at the 7th postoperative day between intervention groups. Results We have enrolled a total of 95 patients, 50 in Group A and 45 in Group B. Fourteen patients were lost to follow up. Eventually, 41 patients in group A and 40 in Group B were available for final analysis. Mean age in months (A = 79.5; SD = 33.9/B = 81.1; SD = 32.6) and sex (A = 58% male; B = 64.4% male) were equivalent between groups. Pain, evaluated through visual analog scale in the 3rd (A = 2.0; IQR 1-6/B = 4.5; IQR 2-6; p = 0.18) and in the 7th (A = 1.0; IQR 1.0-4.5/B = 2.0; IQR 1.0-4.7; p = 0.29) postoperative days, was not different between groups, as was the amount of analgesics administered. Dietary and physical activity patterns also showed no statistically significant differences between groups. Conclusion Dietary and activity restriction after adenotonsillectomy does not seem to affect patients' recovery. Such information may impact considerably on the social aspects that involve a tonsillectomy, reducing the working days lost by parents and accelerating the return of children to school.